Representatives Illocutionary Act Found in Wednesday Addams Movie - Lidvina Mbembo; I Gusti Ayu Agung Sintha Satwika (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study explores representative speech acts in the Wednesday Addams movie, analyzing their frequency, types, and functions. The primary goal of the research is to analyze how representative speech acts are used in character dialogue to conve beliefs, intentions, personalities, and to understand their contribution to narrative and character development. Employing Yule's (1996) classification and Leech's (1983) theory, the study identifies 25 instances of representative speech acts categorized into statements of fact, assertions, conclusions, and descriptions. Statements of fact were found to be the most frequent (32%), followed by descriptions (28%), assertions (20%), and conclusions (20%). These representative speech acts provide significant insights into the characters’ beliefs, intentions, and personalities, contributing to the narrative and character development of the film. The study also compares findings with previous research, indicating that while prior studies have focused on broader speech acts, this research narrows its focus to representative speech acts, offering a more detailed understanding of their role in character dialogue and storytelling. A qualitative descriptive method was applied by analyzing the dialogue in the Wednesday Addams script. This study explores how language is used in movies, especially in modern movie.